Faktor Penyebab Kekerasan Dalam Rumah Tangga Terhadap Perempuan Di Indonesia - Belvina Azahra; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
A considerable number of Indonesians are encountering challenges within their households. In 2023, 6,480 (or 79%) of the 8,234 reported KDRT cases to Komnas Perempuan and its affiliates occurred within the premises of the tangga house. As of 3.221 inside, the kerasan in the staircase of the house has attained its maximum capacity. This research aims to elucidate the origins and impacts of violence within Indonesian households, specifically focusing on the behaviors of the perpetrator and their family members, interpreting the underlying causes of the issue, and examining the perceptions shaped by the relevant perspective, along with the perpetrator's insights regarding the repercussions of the problem. The present study employs both conceptual and normative-legal sources of information. The study's findings indicate that the violence occurring within the household staircase can consist of various sources. The theoretical framework concerning social isolation, control, resources, and ecosystems is readily comprehensible due to several reasons discussed herein. The use of violence by perpetrators, whether through bare hands or other instruments, has the potential to be exacerbated by physical aggression occurring in proximity to the residence, potentially surpassing the severity of the violence within the home itself. Injury or even death may result from the occurrence of violence within the staircase house.